Audience responses to real media violence : the knockout game - Antony, Mary Grace (Lexington Books, 2015)
"Audience Responses to Real Media Violence: The Knockout Game considers an emerging and relatively overlooked area of media effects research: user-generated cellphone videos that feature real violence and its victims. Focusing specifically on a recent sinister media trend known as the Knockout Game, Mary Grace Antony explores how audiences respond to the victims in these videos. How do we assess the realism of this violence? And how do these evaluations of realism in turn influence our feelings of empathy and concern for the victims of violence? The burgeoning abundance and availability of real media violence online makes these questions more relevant today than ever before, and illustrates our complex responses to new and emerging media subgenres."--Back cover